Making the most of activity-based costing: case of compensation management at a Korean public university - Lau, Yeng Wai; Alimun, Nuzul (Universiti Putra Malaysia Press, 2014)
Activity-based costing (ABC) has been touted as being able to provide insights into profitability by segregating revenues and costs into the various activities that give rise to them. However, empirical findings on the performance benefits of ABC are mixed. This paper demonstrates how to make the most of ABC in evaluating costs of flexible, part-time versus committed, full-time teaching resources at a Korean public university. Unattractive compensation packages in academia is an issue of concern that leads to a range of problems from shortage of staff in academia to street protests and even suicides in South Korea. The structured, cause-and-effect approach of ABC provides insights into various avenues for improvement in the university's performance evaluation system and compensation packages to facilitate better deployment of flexible and committed teaching resources.